Evaluation of the Effect of Different Contaminants on the Shear Bond Strength of Different Adhesive Systems - An In Vitro Study - Monalisha Jha; Amit Kumar; Abha Telang; Puja Kumari; Gaurav Verma; Karuna Bharti (Journal of Pharmacy and Bioallied Sciences)
Background: The bonding of restorative materials to tooth structure is made easier by dental adhesive solutions, which are essential in restorative dentistry. Nonetheless, there are a number of things that can affect how well they operate, such as oral environmental contaminants. Methodology: The research utilized a regulated experimental framework, segmenting the samples into smaller groups to symbolize discrete contamination scenarios observed in dentistry settings, such as artificial saliva and Viscostat clear contamination prior to and following bonding agent curing. The adhesive groups consisted of three subgroups: ADPER SINGLE BOND-2, CLEARFIL LINER BOND-F, AND SINGLE BOND UNIVERSAL ADHESIVE. Each subgroup had 11 samples. To assess the variations in shear bond strength across the groups, statistical analysis was applied, most likely using SPSS or a comparable program. Results: In all contamination circumstances, ADPER SINGLE BOND-2 consistently showed a stronger shear bond strength than CLEARFIL LINER BOND-F and SINGLE BOND UNIVERSAL ADHESIVE, according to the data. To be more precise, ADPER SINGLE BOND-2 showed better results even when artificial saliva and Viscostat clear were present, suggesting that it might be used in clinical settings. These results highlight how crucial adhesive choice is to get the best bonding results possible in restorative dentistry. Conclusion: According to the study, ADPER SINGLE BOND-2 may provide medical professionals with a dependable solution for creating strong, long-lasting adhesive connections, especially in difficult clinical settings where contamination is a possibility.